The economic evaluation of a bicycle-sharing scheme for school and university destined commuter traffic in Stellenbosch, South Africa that is proposed as a sustainable mode of transport to relieve traffic congestion: A case study for the R44 inbound traffic from Somerset West - Ter Huurne, Dominique Andrea (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScEng)--Stellenbosch University, 2016.